Práticas de formação da EJA: as vozes entrecruzadas de professores de matemática e de licenciandos no estágio supervisionado - Silva, Jeane do Socorro Costa da (2014)
This research of qualitative type sought to identify both the difficulties faced by Mathematics teachers who teach young people and adults classes in the metropolitan area of Belem-Para and the perceptions of Mathematics undergraduate students on the reality of this type of teaching considering what they observed in the intership. This thesis was guided by the following research question: what common elements bring the voices of teachers and undergraduate students in order to contribute to a reflexive practice from the subjects Teaching Practice and Supervised Internship of Para State University- UEPA, based on the interlocution between school and university? The study aimed at analyzing the voices of experienced teachers and beginning teachers in relation to the challenges of the practice of the formers and to the opportunities of coexistence and confrontation of these challenges even during the training process. The theoretical frameworks of this research were grounded on: Garcia, Imbernón, Nóvoa, Tardif, Zeichner e Pimenta e Lima, concerning the initial training based on the approach between university and school, grounded on the scope of practice in a reflexive perspective; and on Haddad e Di Pierro, Gadotti, Haddad, Ribeiro, Arroyo, Galvão e Di Pierro, Fonseca e Barcelos, to discuss the bases of EJA and the teaching of Mathematics in this segment. The main characters of this research were two teachers of Mathematics who work in EJA classes and four trainees of Undergraduation Course of Mathematics of UEPA. Also took part of this study fifty and seven teachers of Mathematics who work in EJA classes around the metropolitan area of Belem and fourteen undergarduate students of Mathematics course. The research revealed the importance of the participation and insertion of future teachers in different segments of teaching, such as Young and Adult Education EJA; and it also showed the importance of giving voice to the Mathematics teacher who is working with EJA classes in Belem. The results contributed to think the intership based on the analysis and reflection of teaching practice experienced in it, in order to rebuild the views, beliefs and assumptions on EJA modality, with the support of the theoretical fundamentals. The reasearch revealed the importance of planning a lesson taking into account the specific characteristics of EJA students and the previous knowledge brought by them, whether school and life experience; it also allowed the trainees to experience some difficulties related to the teaching of Mathematics in EJA classes and to seek solutions to overcome them; and at last, it enabled an approach between school and university and a link between the theoretical and practical aspects. These results imply changes of an institutional culture grounded on problematization, discussion, decision-making by the university on the basis of a regional need and with a view to ensuring the rights of citizens to attend a quality school, even outside the expected regular time